La réglementation : la pointe de l’Iceberg - Moreau, Rémi; Dumais, Christian N. (Assurances)

(untitled) (HEC Montréal, 1983)
The following article written by lawyers Rémi Moreau and Christian N. Dumais describes various problems caused by regulations, which are growing more complex and wide-sweeping. This article is of particular interest as it deals with certain aspects which are to be studied by a government Commission.